ISOLASI DAN IDENTIFIKASI SENYAWA ANTIOKSIDAN DARI BATANG PAKIS (ALSOPHILA GLAUCA J.SM) DENGAN METODE DPPH (2,2-DIFENIL-1- PIKRILHIDRAZIL) - Sri Wahdaningsih; Subagus Wahyuono; Erna Prawita Setyowati (Kaunia: Integration and Interconnection Islam and Science, 2013)
Oxidative stress induced by the radicals have been known to affect the occurrence of various degenerative disease. As the search for natural antioxidant compounds had been studied the isolation and identification of antioxidant compounds in fern stems (Alsophila glauca J.Sm) using DPPH method (1,1-diphenyl 2-picrylhydrazyl). Fern stem extraction was done by maceration with wasbenzen and metanol. Extracts was obtained by evaporating the wasbenzen solvent with a rotavapor. Material was re-macerated with methanol after all wasbenzen evaporation. The same way was done on  wasbenzen to obtain the metanol extract. These extracts were tested for antioxidant activity using DPPH method with TLC. Active extract was partitioned in 80% methanol. Extracts both soluble and insoluble in methanol 80% were tested their antioxidant activity using DPPH method (TLC). Active extract was fractionated in vacuum liquid chromatography using a mobile phase with different polarity gradient and different concentrations (wasbenzen:chloroform). Active  fraction  was  isolated  by  preparative TLC method and purity of compounds obtained was tested by TLC. Antioxidant activity of isolates obtained were tested by DPPH method using spectrophotometry. Compounds known to had antioxidant activity as radical catcher with IC50 178.4 µg/ml.